POP-UP BOOK AS A MEDIA THROUGH MOTHER EMPOWERMENT - Ninawati; Pribadi, Natasha; Khamila, Aurora Nurul; W, Raden Ajeng Astari A. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Baby blues syndrome is a mental health disorder such as emotional instability in postpartum mothers. Generally, this condition often occurs for three to fourteen days postpartum, it is characterized by difficulty sleeping, changes in mood and appetite, reduced interest in daily activities, and fatigue. Several factors can influence this condition, such as socio-economic factors, lack of support from the supposed support system, education, imbalanced hormones after childbirth, to the trauma experienced during childbirth. Lack of preparation and support for the mother in dealing with the baby blues can lead to more acute symptoms in the form of postpartum depression. Maternal knowledge and actions in dealing with and anticipating the occurrence of baby blues are essential for mothers and babies. This effort can be obtained by one of the ways is through self-empowerment by the mother. In order to provide internal support, a pop-up book for student creativity program (PKM) was designed that aims to educate and provide emotional support to mothers, especially on several interventions and therapies that can be done independently. This pop-up book is made as a development of educational media in the form of interactive books carried out by conducting in-depth analysis of influencing factors and variables, examining the various types of therapies available, and designing products. The main focus of this design is expected that mothers who have the potential to experience baby blues syndrome as a potential target audience can understand the phenomenon of baby blues more deeply and as a form of prevention effort from baby blues syndrome ABSTRAK Sindrom baby blues merupakan suatu gangguan kesehatan mental seperti kondisi emosi yang tidak stabil pada ibu pasca melahirkan. Umumnya, kondisi ini seringkali terjadi selama tiga hingga empat belas hari pasca melahirkan, hal tersebut ditandai dengan kesulitan tidur, perubahan pada suasana hati, perubahan nafsu makan, berkurangnya minat pada kegiatan sehari-hari, hingga mudah lelah. Beberapa faktor yang diduga dapat mempengaruhi kondisi ini, antara lain seperti faktor sosio-ekonomi, kurangnya dukungan dari support system, edukasi, hormon yang masih belum seimbang pasca melahirkan, sampai pada trauma yang dialami saat menjalani persalinan. Minimnya persiapan maupun dukungan bagi sang ibu dalam menghadapi baby blues dapat mengakibatkan gejala yang lebih akut dalam bentuk depresi postpartum. Pengetahuan dan tindakan ibu dalam menghadapi dan mengantisipasi terjadinya baby blues merupakan suatu hal yang penting bagi ibu dan bayi. Upaya ini dapat diperoleh dengan salah satunya caranya adalah melalui pemberdayaan diri oleh sang ibu. Guna memberikan dukungan secara internal maka pop-up book untuk PKM dibuat yang bertujuan untuk mengedukasi dan memberikan dukungan emosional pada ibu terutama pada beberapa intervensi dan terapi yang dapat dilakukan secara mandiri. Pop-up book ini dibuat dengan literature review, melalui analisis faktor dan variabel yang mempengaruhi, menelaah ragam jenis terapi yang tersedia, serta melakukan perancangan produk. Fokus utama perancangan ini diharapkan ibu yang memiliki potensi mengalami sindrom baby blues sebagai calon khalayak sasaran dapat memahami fenomena baby blues secara lebih dalam dan sebagai bentuk upaya pencegahan dari sindrom baby blues